2021
DOI: 10.1038/s41598-020-80230-3
|View full text |Cite
|
Sign up to set email alerts
|

The shifted balance of arginine metabolites in acute myocardial infarction patients and its clinical relevance

Abstract: The arginine metabolism as a target for cardioprotection in patients with ST-segment elevation myocardial infarction (STEMI) remains insufficiently understood. Arginine, ornithine, citrulline, asymmetric dimethylarginine (ADMA) and proline plasma levels were measured using liquid chromatography and tandem mass spectrometry in 70 consecutive STEMI patients upon admission and at 6-month follow-up and were compared with left ventricular function, volumes, and infarct characteristics determined by cardiac magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Arginine is one of the most adaptable amino acid which acts as a precursor for protein, nitric oxide, polyamines, urea, glutamate, proline, agmatine and creatinine 21 . Lower arginine availability has been earlier reported to be associated with cardiovascular risk 22 . Proline and hydroxyproline are amino acids which help in maintaining cell structure and functions.…”
Section: Discussionmentioning
confidence: 91%
“…Arginine is one of the most adaptable amino acid which acts as a precursor for protein, nitric oxide, polyamines, urea, glutamate, proline, agmatine and creatinine 21 . Lower arginine availability has been earlier reported to be associated with cardiovascular risk 22 . Proline and hydroxyproline are amino acids which help in maintaining cell structure and functions.…”
Section: Discussionmentioning
confidence: 91%
“…Many of these ‘adaptative immune response’ pathway members, and those involved in TCR signalling in particular, were negatively correlated ( Figure ) with both arginase gene transcripts (ARG1 and ARG2); which were 14%–16% more abundant in those that subsequently died (online supplementary Table ). Arginase degrades arginine and decreased arginine, preceded by a measurable increase in arginase activity, is associated with poorer 6‐month outcomes in patients with ST‐elevation myocardial infarction 19 . Arginase gene expression, induced by lactate production consequent to hypoxia, can limit T‐cell proliferation 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Arginase degrades arginine and decreased arginine, preceded by a measurable increase in arginase activity, is associated with poorer 6-month outcomes in patients with ST-elevation myocardial infarction. 19 Arginase gene expression, induced by lactate production consequent to hypoxia, can limit T-cell proliferation. 20 A negative association between ARG2 and the pro-survival IL-7 receptor (IL7R/CD127) was observed in survivors (Figure 3A) potentially linking arginine metabolism and IL7R signalling role in T-cell survival and memory responses.…”
Section: Altered Biological Pathways and Prognosis In Heart Failurementioning
confidence: 99%
“…A clinical investigation demonstrated that the expression level of arginase (ARG1) is elevated in individuals with STEMI and that it serves as an indicator of plaque susceptibility and has a correlation with infarction size in the clinical progression of this disease [50]. The underlying mechanism is that ARG1 lowers NO bioavailability and leads to atherosclerosis by depleting its common substrate (L-arginine) [51]. In acute MI, reduced NO bioavailability leads to endothelial impairment, plaque destabilization, and greater vulnerability to ischemia-reperfusion damage [52].…”
Section: Discussionmentioning
confidence: 99%